2020
DOI: 10.1111/jgs.16880
|View full text |Cite
|
Sign up to set email alerts
|

Fingerstick Glucose Monitoring in Veterans Affairs Nursing Home Residents with Diabetes Mellitus

Abstract: BACKGROUND/OBJECTIVE Guidelines recommend less intensive glycemic treatment and less frequent glucose monitoring for nursing home (NH) residents. However, little is known about the frequency of fingerstick (FS) glucose monitoring in this population. Our objective was to examine the frequency of FS glucose monitoring in Veterans Affairs (VA) NH residents with diabetes mellitus, type II (T2DM). DESIGN AND SETTING National retrospective cohort study in 140 VA NHs. PARTICIPANTS NH residents with T2DM and older tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…While residents with higher levels of cognitive impairment received fewer fingersticks overall and in some GLM categories, the differences were relatively small suggesting that cognitive status may be a minor consideration in fingerstick monitoring decisions. Our results are aligned with a previous study in VA NH residents recently discharged from the hospital documenting the high burden of fingerstick monitoring 13 . We extend these results by demonstrating that fingersticks occur more frequently than recommended by guidelines across cognitive impairment levels in NH residents at day 31 after NH admission 4 …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…While residents with higher levels of cognitive impairment received fewer fingersticks overall and in some GLM categories, the differences were relatively small suggesting that cognitive status may be a minor consideration in fingerstick monitoring decisions. Our results are aligned with a previous study in VA NH residents recently discharged from the hospital documenting the high burden of fingerstick monitoring 13 . We extend these results by demonstrating that fingersticks occur more frequently than recommended by guidelines across cognitive impairment levels in NH residents at day 31 after NH admission 4 …”
Section: Discussionsupporting
confidence: 89%
“…Our results are aligned with a previous study in VA NH residents recently discharged from the hospital documenting the high burden of fingerstick monitoring. 13 We extend these results by demonstrating that fingersticks occur more frequently than recommended by guidelines across cognitive impairment levels in NH residents at day 31 after NH admission. 4 Previous studies have found that individuals with severe cognitive impairment often receive high hypoglycemia risk GLMs, which can result in adverse events.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations